Heraclitus B 32 Revisited in the Light of the Derveni Papyrus - Bossi, Beatriz (Anales del Seminario de Historia de la Filosofía, 2011)
The objective of this article is to consider whether the Commentator of the Derveni Papyrus can contribute to our understanding of the double divine will to reject and accept the name of Zeus. After examining some inconsistencies that the traditional readings raise, the authoress appeals to the Derveni Papyrus in order to offer an alternative diachronic interpretation. On this reading, the unique wise one, in the first place, does not wish to be called by the name of Zeus because this name ascribes birth and diversification to it, while it is, as such, eternal and simple. On the other hand, as it cyclically becomes multiple, it is also willing to be identified with Zeus, the God who, according to the Papyrus, swallowed his Grandfather’s phallus along with Mind, got pregnant of everything and re-created the universe. This account fits with Heraclitus’ doctrine that there is no creation of the world but some kind of derivation of it from the one, and vice-versa.